103k views
4 votes
Solve by any method (substitution, graphing, linear combination y=x−6 3x+2y=8 (14,8) (0,-6) (4,-2) (3,-3)

2 Answers

5 votes

Answer:

The answer is (4,-2)

Explanation:

y=x-6

3x+2y=8

3x+2(x-6)=8

3x+2x-12=8 Combine like terms

3x+2x-12+12=8+12 add 12 to both sides then combine

5x=20→ x=4

then plug it in to y=x-6→y=4-6→y=-2

User Markthethomas
by
4.9k points
5 votes

Answer:

(4,-2)

Step by Step Explanation:

Given equations are

y=x-6 eq(1)

3x+2y=8 eq(2)

Subtitute eq(1) into eq(2) we get

3x+2(x-6)=8

3x+2x-12=8

5x-12=8

Adding 12 on both side of equation we get

5x-12+12=8+12

5x=20

Dividing by 5 on both sides of equation we get

5x/5=20/5

x=4

Putting the value of in eq(1) we get

y=4-6

y=-2

The solution is (4,-2).



User JohannesH
by
6.4k points